ANALISIS PLTS ATAP 25 KWP ON GRID KANTOR DPRD PROVINSI BALI - I Kadek Hendy Wijaya; I Nyoman Satya Kumara; Wayan Gede Ariastina (Program Studi Teknik Elektro UNUD, 2022)
Development to new renewable energy still lower than Indonesia's target of 23% in 2025. For this reason, alternative solutions are needed, namely the use of renewable energy, one of which is from the solar energy sector, namely solar PV. Solar energy has the highest potential compared to other renewable energy sectors of 207.9 GW. Based on that, in 2020 the Province of Bali received a Rooftop Solar PV grant through the Ministry of Energy and Mineral Resources, one of which is located at the Bali Provincial DPRD Government Office with an installed power of 25 kWp using the On Grid system. Based on this, it is necessary to conduct a detailed study of the potential, operational systems, savings and the proper management model of Rooftop Solar PV at the Bali Provincial DPRD Office. The potential of Solar PV electricity production on the roof of the Bali Provincial DPRD Office was analyzed by simulating the orientation and tilt angle of the Solar PV to get the optimum Solar PV electrical energy production results using HelioScope software. The results showed that the results of electrical energy production in the simulations of the two scenarios tended to be higher with the total difference in scenario 1 and scenario 2 being 21.75% and 19.66%, respectively. For savings that can be obtained for 6 months of Rp. 36,055,301 with a percentage of 22.60%. The PLTS management model in the future is located in the general section, precisely in the Sub Coordinator of the Equipment, Assets and Household Substance Unit.